Recursos genéticos de arroz (Oryza sativa L.) no sul do Brasil. - Magalhães Júnior, Ariano Martins de (2007)
The worldwide adaptability of rice, allied to constant research efforts, reassures its grain a place among the major staple foods for humankind. The influence of natural selection resulted in a wide diversity in the Oryza genus, which is currently composed by 23 species. On the other hand, only O. sativa L. (asian cultivated rice) and O. glaberrima (african cultivated rice) have been used for human consumption, therefore, subjected to artificial selection. The process of domestication in rice has selected important agronomic characters for better plant performance in specific environments, resulting in a bottleneck effect on the genetic diversity. This effect makes a change in the initial gene pool, keeping some selected genes and eliminating others. Thus, the objective of this work was to amplify the genetic basis of rice in southern Brazil, through collections and introductions, characterization of accessions and estimation of genetic distances between accessions. The results revealed a limited number of rice landraces in the state of Rio Grande do Sul. These landraces are found in small farms that still keep these genotypes for their own consumption. A large area of the state is cultivated with modern phillipine-type varieties. However, the rescued landrace genotypes present genetic variability for a large number of the evaluated characters, and may serve as source of genes for breeding programs. The descriptors used for the multivariate analysis were efficient to distinguish the collected accessions, to identify duplicated genotypes in the collection as well as for phenotyping the whole collection. The estimate of genetic distance was obtained using Mahalanobis (D2), distance, which indicated a tight clustering of cultivars released by Embrapa Temperate Climate. The genetic distance matrices based on field- and greenhouse-measured qualitative characters as well as on the joint analysis showed high degree of association, indicating that many characters can be selected based on only one of these criteria. Similar results were obtained for quantitative characters.